Aloin isoforms (A and B) selectively inhibits proteolytic and deubiquitinating activity of papain like protease (PLpro) of SARS-CoV-2 in vitro - Devin S. M. Lewis; Joanna Ho; Savannah Wills; Anasha Kawall; Avini Sharma; Krishna Chavada; Maximilian C. C. J. C. Ebert; Stefania Evoli; Ajay Singh; Srujana Rayalam; Vicky Mody; Shashidharamurthy Taval (Scientific Reports, 2022)
Abstract The most common host entry point of human adapted coronaviruses (CoV) including SARS-CoV-2 is through the initial colonization in the nostril and mouth region which is responsible for spread of the infection. Most recent studies suggest that the commercially available oral and nasal rinse products are effective in inhibiting the viral replication. However, the anti-viral mechanism of the active ingredients present in the oral rinses have not been studied. In the present study, we have assessed in vitro enzymatic inhibitory activity of active ingredients in the oral mouth rinse products: aloin A and B, chlorhexidine, eucalyptol, hexetidine, menthol, triclosan, methyl salicylate, sodium fluoride and povidone, against two important proteases of SARS-CoV-2 PLpro and 3CLpro. Our results indicate only aloin A and B effectively inhibited proteolytic activity of PLpro with an IC50 of 13.16 and 16.08 μM. Interestingly, neither of the aloin isoforms inhibited 3CLpro enzymatic activity. Computational structural modelling of aloin A and B interaction with PLpro revealed that, both aloin isoforms form hydrogen bond with Tyr268 of PLpro, which is critical for their proteolytic activity. Furthermore, 100 ns molecular dynamics (MD) simulation studies predicted that both aloin isoforms have strong interaction with Glu167, which is required for PLpro deubiquitination activity. Our results from the in vitro deubiquitinase inhibition assay show that aloin A and B isomers exhibit deubiquitination inhibitory activity with an IC50 value of 15.68 and 17.51 µM, respectively. In conclusion, the isoforms of aloin inhibit both proteolytic and the deubiquitinating activity of SARS-CoV-2 PLpro, suggesting potential in inhibiting the replication of SARS-CoV-2 virus.